RELIGION, FAITH AND PSYCHIATRY (A REVIEW) - Sousa, Avinash De (Journal of Pakistan Psychiatric Society, 2007)
This article aims to explore the relationships between religion and psychiatry, its implications for the treatment of mental disorders, the use of religion, religious beliefs and spiritual texts in psycho therapy and clinical psychiatric practice. This article tries to bring out the importance and relevance of religion and spirituality into modern day clinical practice. Key words: Religion, Faith, Psychiatry.